A FUNCTIONAL APPROACH TO THE INSURANCE INDUSTRY - Briys, Eric; de Varenne, François (Assurances)

(untitled) (HEC Montréal, 2000)
Despite the all-embracing nature of the term "financial services", there is a clear distinction in most people’s mind between, for instance, the status of policyholders and bank customers. lndeed, the mere existence of banks and insurance companies is taken for granted. This being said, the recent changes - not to say upheavals - that have shaken the world of financial markets and institutions call for a drastic revision of our perception and understanding of the role of financial institutions. The financial markets have developed a steadily growing range of instruments and techniques that have boosted their roles in our economies. Many observers do question the benefits of this massive expansion of what they call "the virtual economy". For instance, they claim that the current pace of financial innovations may eventually lead to an increase in systemic risk. They fear significant disruptions that the proliferation of derivatives may cause to the real economy. This article challenges this view. It focuses primarily on insurance companies. Insurance policies and put options are very close relatives. This parenthood carries far-reaching implications that we try to explore in the following pages.